Analysis on the thermal decomposition kinetics and storage period of biomass-based lycorine galanthamine - Qin, Chong; Ling, Weihong; Tian, Chunlian (Frontiers in Chemistry, 2023)
As global ageing deepens and galanthamine is the preferred clinical drug for the treatment of mild to moderate Alzheimer's disease, it will be valuable to examine the behaviour and mechanism of galanthamine's thermal decomposition for its quality control, formulation process, evaluation of thermal stability and expiry date in production. In order to study the pyrolysis of galanthamine hydrobromide with nitrogen as the carrier gas, a thermogravimetric-differential thermogravimetric technique (TG-DTG) was applied at a temperature rise rate of 10 K min-1 and a volume flow rate of 35 mL min-1. The apparent activation energy Ea and the prefactor A (Ea = 224.45 kJ mol-1 and lnA = 47.40) of the thermal decomposition reaction of galanthamine hydrobromide were calculated according to the multiple heating rate method (Kissinger and Ozawa) and the single heating rate method (Coats-Redfern and Achar), and the most probable mechanism function was derived, and then the storage period was inferred from Ea and E. A three-dimensional diffusion mechanism was suggested to control the thermal decomposition of galanthamine hydrobromide in accordance with the Jander equation, random nucleation and subsequent growth control, corresponding to the Mample one-way rule and the Avrami-Erofeev equation. As a result, the thermal decomposition temperature of galanthamine hydrobromide gradually increased with the rate of temperature rise. From Gaussian simulations and thermogravimetric data, galanthamine hydrobromide decomposed at the first stage (518.25 K to 560.75 K) to release H2O, at the second stage (563.25 K to 650.75 K) to generate CO, CO2, NH3 and other gases, and finally at the third stage (653.25 K to 843.25 K) to release CO2. After 843.25 K, the residual molecular skeleton is cleaved to release CO2 and H2O. According to the Ea and A presenting in the first stage of thermal decomposition, it is assumed that the storage life of galanthamine hydrobromide at room temperature 298.15 K is 4 to 5 years.